Liderazgo transformacional del director y desempeño docente en una institución educativa – distrito de Chao, 2020 - Vega Castro, Paola Janeth (2023)
The purpose of this research was to determine the correlation between the transformational leadership of the director and the teaching performance in an educational institution - Chao district, 2020, where the relationship between the transformational leadership of the director and the teaching performance of an educational institution was examined. A population of 46 teachers was considered, where the type of sampling was a census. In addition, for data collection, the survey was used as a technique and its instrument the questionnaire, which was composed of 20 items related to the transformational leadership variable and 28 items related to the teacher performance variable according to the Likert scale; These were validated through the appreciation of items through the modified item-test correspondence formula with values between .753 to .910, greater than .20, in the director's transformational leadership test and values between 0.390 to 0.731, greater than 0.20 in test to assess teacher performance. In conclusion, through the demonstration of convenience of Spearman's rho that there is a significant relationship of 0.450 (p<0.01), direct of medium magnitude, between the transformational domain of the director with the academic performance of teachers.